A Comparative Study of the Photosensitizer Penetration into Artificial Caries Lesions in Dentin Measured by the Confocal Raman Microscopy. (25th November 2013) - Melo, Mary Anne S.; Rolim, Juliana P.M.L.; Zanin, Iriana C.J.; Silva, José J.A.; Paschoal, Alexandre R.; Ayala, Alejandro P.; Rodrigues, Lidiany K.A.
Abstract This study utilized the confocal Raman microspectroscopy (CRM) technique for the first time to investigate the degree of the penetration of toluidine blue‐orto (TBO) in artificial caries lesions produced by two distinct caries‐inducing models. The dentin specimens (n = 10) were divided into three groups: control, in vitro and in situ. Thereafter, the lesion depth and the demineralization level were evaluated by cross‐sectional microhardness (CSMH). CRM mapping across the dentin surface was assessed after the dye application. The CSMH and CRM data were analyzed by t‐test and ANOVA, respectively (P < 0.05). The values of the lesion depth and the demineralization areas were higher for in situ samples (P < 0.05). The TBO penetration values (μm) for the control, in vitro and in situ groups were 44.8 ± 5.6, 46.1 ± 4.5 and 51.2 ± 8.5, respectively. There were no statistically significant differences among the groups (P > 0.05). The rate of TBO penetration was detected up to about <50 μm and the demineralization level did not influence the results. These results have showed promising parameters to develop new protocols for deep caries lesions management using photodynamic antimicrobial chemotherapy.